Synthesis and Antiradical Activity of Isoquercitrin Esters with Aromatic Acids and Their Homologues - Heřmánková-Vavříková, Eva; Křenková, Alena; Petrásková, Lucie; Chambers, Christopher Steven; Zápal, Jakub; Kuzma, Marek; Valentová, Kateřina; Křen, Vladimír (International journal of molecular sciences, 2017)
Isoquercitrin, (IQ, quercetin-3-O-β-d-glucopyranoside) is known for strong chemoprotectant activities. Acylation of flavonoid glucosides with carboxylic acids containing an aromatic ring brings entirely new properties to these compounds. Here, we describe the chemical and enzymatic synthesis of a series of IQ derivatives at the C-6″. IQ benzoate, phenylacetate, phenylpropanoate and cinnamate were prepared from respective vinyl esters using Novozym 435 (Lipase B from Candida antarctica immobilized on acrylic resin). The enzymatic procedure gave no products with "hydroxyaromatic" acids, their vinyl esters nor with their benzyl-protected forms. A chemical protection/deprotection method using Steglich reaction yielded IQ 4-hydroxybenzoate, vanillate and gallate. In case of p-coumaric, caffeic, and ferulic acid, the deprotection lead to the saturation of the double bonds at the phenylpropanoic moiety and yielded 4-hydroxy-, 3,4-dihydroxy- and 3-methoxy-4-hydroxy-phenylpropanoates. Reducing capacity of the cinnamate, gallate and 4-hydroxyphenylpropanoate towards Folin-Ciocalteau reagent was significantly lower than that of IQ, while other derivatives displayed slightly better or comparable capacity. Compared to isoquercitrin, most derivatives were less active in 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging, but they showed significantly better 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid, ABTS) scavenging activity and were substantially more active in the inhibition of tert-butylhydroperoxide induced lipid peroxidation of rat liver microsomes. The most active compounds were the hydroxyphenylpropanoates.
Keywords: Free Radical Scavengers; quercetin; cinnamic acid; Esters; vysokoúčinná kapalinová chromatografie; Molecular Structure; aromatic acid; isoquercitrin; antioxidant activity; lipoperoxidation; hmotnostní spektrometrie; peroxidace lipidů; molekulární struktura; Chromatography, High Pressure Liquid; Lipid Peroxidation; Nuclear Magnetic Resonance, Biomolecular; DPPH; gallic acid; scavengery volných radikálů; Novozym 435; nukleární magnetická rezonance biomolekulární; lipase; Mass Spectrometry; estery; Quercetin